Erratum: Geopolitical position of the PR of China: State and perspectives (vol. 59, br.1, str. 205-225) - Editorial board (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
In the paper “Geopolitical Position of the PR China – State and Perspectives”, published in the Collected Papers, Faculty of Law in Novi Sad, No. 1/2025, pp. 205–225 (https://doi.org/10.5937/zrpfns59-56831), a technical error occurred in the order of authors’ names. The incorrect order appears: • on the title page in both Serbian (p. 205) and English (p. 225), • in the headers on even-numbered pages (pp. 206, 208, 210, 212, 214, 216, 218, 220, 222, 224), • and in the table of contents (p. V). The correct order of authors is: Ljubomir Stajić, Vladan Mirković, Nenad Radivojević. The Editorial Board apologizes to the authors and readers for the error.